Species-specific evolution of telomeric and rDNA repeats in the tobacco composite genome - Kovařik, A; Fajkus, J; Koukalová, B; Bezděk, M (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 1996)
In order to investigate possible interactions between parental genomes in the composite genome of Nicotiana tabacum we have analyzed the organization of telomeric (TTTAGGG)n and ribosomal gene (rDNA) repeats in the progenitor genomes Nicotiana sylvestris and Nicotiana tomentosiformis or Nicotiana otophora. Telomeric arrays in the Nicotiana species tested are heterogeneous in length ranging from 20 to 200 kb in N. sylvestris, from 20 to 50 kb in N. tomentosiformis, from 15 to 100kb in N. otophora, and from 40 to 160kb in N. tabacum. The patterns of rDNA repeats (18S, 5.8S, 25S RNA) appeared to be highly homogeneous and speciesspecific; no parental rDNA units corresponding to N. sylvestris, N. tomentosiformis or N. otophora were found in the genome of N. tabacum by Southern hybridization. The results provide evidence for a species-specific evolution of telomeric and ribosomal repeats in the tobacco composite genome.